ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል አምስት - International Livestock Research Institute (International Livestock Research Institute, 2022)
In episode five, which aired on Debre Birhan Fana FM 94.0 on 19 July 2022, farmers in the North Shewa Moret and Jiru District shared their experiences with the feed trough technology and its benefits. Zembaba Telila and Mezigebu Getachew, livestock experts in North Shewa, explained how they are working with Africa RISING and AICCRA projects to promote the use of feed troughs by livestock farmers in the area.